Problems and prospects of deepening EU-Ukrainian relations - Латковський, Павло Павлович; Латковський, П. П.; Латковский, Павел Павлович; Latkovskyi, Pavlo P.; Марущак, Анна Валеріївна; Марущак, А. В.; Марущак, Анна Валерьевна; Marushchak, Anna V. (Baltija Publishing, 2019)
Three countries: Georgia, Moldova, and Ukraine have concluded European Union Association Agreements, under similar terms and conditions of European Partnership. Analytical review allowed determining that in their political integrative development, they have similar problems and ways to overcome them. They are distinguished by a relatively high level of democratic freedoms and political pluralism; however, none of them can be considered as a consolidated democracy, these countries have hybrid political regimes. Among the main obstacles occurring on the way of their integration processes, one can distinguish problems associated with ethical, regional, and cultural conflicts; specific features of the formation of constitutional systems; features of the formation of PR technologies of government and society; deep-rooted corruption and influence of oligarchs in party systems and, as a consequence, propensity to use non-constitutional means of political struggle and economic development. Despite these structural problems, favouring European values and norms demonstrated by societies of the three countries holds the promise of consolidating democratic institutions and overcoming problems. The purpose of the article is to determine problems and prospects of deepening relations of the EU with three countries: Ukraine, Moldova, and Georgia, and to substantiate theses stating that consistent and reinforced integration of the European Union in this region is crucial for further success and development of all actors of this process. Georgia, Moldova, and Ukraine do not compose a single region (both in a geographical and economic context); however, since 2014 they are developing according to the same scenarios. Their aspiration to integration has provoked problems in relations with Russia and intensified opposition to the policy of Europeanisation within the countries. In Ukraine, the most difficult and severe events took place: it passed through government overthrow, loss of territory, and military actions in Donbas caused by Russia, which continue to this day. For Moldova and Georgia, the choice of democratic imperatives also had grave consequences. In Georgia, they were identified as two long-term wars for the separation in Abkhazia and South Ossetia; ended with the defeat of central authorities and creation of two unrecognized states. Moldova has faced a similar problem in Transnistria in 1992. In all countries, Russian armed forces were important actors who played an important role in determining the results of these conflicts. According to the Democracy Index, Moldova is evaluated as “imperfect democracy”; Georgia – as “hybrid regime”; Ukraine has moved below, from the category of “imperfect democracy” to the lowest “hybrid regime”. Over the political pressure of Russia, the EU and Ukraine postpone the provisional application of the DCFTA (Deep and Comprehensive Free Trade Area) to January 1, 2019. There are marked positive consequences of Ukrainian export to the EU, which volume has increased by 30% in 2017. The structure of exports to the EU has shifted towards machines and equipment, fats and oils of vegetable or animal origin, ready-made meals, and products of animal origin. The EU share in Ukrainian exports and imports has also increased due to a significant reduction in trade with Russia. The application of the EU tariff quotas for agricultural production has increased over the 2014–2017 years because Ukrainian producers have gradually overcome the problems with food safety and weak demand for their production. European choice is an extremely important factor for continuous democratization of all these three countries. In spite of competition among European and Eurasian identities, each of them considers itself a European country. The choice to continue the path of association with Europe, made by these countries, despite obvious political risks (especially severe for Ukraine), is the best evidence of their real adherence to European development path.

Три країни: Грузія, Молдова та Україна уклали Угоди про асоціацію з Європейським Союзом на подібних умовах Європейського партнерства. Аналітичний огляд дозволив визначити, що в політичному інтегративному розвитку вони мають схожі проблеми та шляхи їх подолання. Їх відрізняє відносно високий рівень демократичних свобод і політичний плюралізм; проте жодна з них не може вважатися консолідованою демократією, ці країни мають гібридні політичні режими. Серед основних перешкод, що виникають на шляху їх інтеграційних процесів, можна виділити проблеми, пов'язані з етичними, регіональними та культурними конфліктами; специфічні особливості формування конституційних систем; особливості формування PR-технологій влади та суспільства; глибоко вкорінена корупція та вплив олігархів у партійних системах і, як наслідок, схильність до використання неконституційних засобів політичної боротьби та економічного розвитку. Незважаючи на ці структурні проблеми, схвалення європейських цінностей і норм, які демонструють суспільства трьох країн, обіцяє консолідацію демократичних інститутів і подолання проблем. Метою статті є визначення проблем і перспектив поглиблення відносин ЄС з трьома країнами: Україною, Молдовою та Грузією, а також обґрунтування тез про те, що послідовна та посилена інтеграція Європейського Союзу в цьому регіоні є визначальною для подальшого успіху і розвитку усіх суб'єктів цього процесу. Грузія, Молдова та Україна не складають єдиного регіону (як в географічному, так і в економічному контексті); проте з 2014 року вони розвиваються за тими ж сценаріями. Їхнє прагнення до інтеграції викликало проблеми у відносинах з Росією та посилило протидію політиці європеїзації всередині країн. В Україні відбулися найважчі та найтяжчі події: це пройшло через повалення уряду, втрату території та військові дії на Донбасі з боку Росії, які тривають і донині. Для Молдови та Грузії вибір демократичних імперативів також мав серйозні наслідки. У Грузії вони були визначені як дві довготривалі війни за відокремлення Абхазії та Південної Осетії; закінчилася поразкою центральних органів влади та створенням двох невизнаних держав. Молдова зіткнулася з подібною проблемою в Придністров'ї в 1992 році. У всіх країнах російські збройні сили були важливими акторами, які відігравали важливу роль у визначенні результатів цих конфліктів. Згідно з індексом демократії, Молдова оцінюється як «недосконала демократія»; Грузія – як «гібридний режим»; Україна просунулася нижче, з категорії «недосконалої демократії» до найнижчого «гібридного режиму». Через політичний тиск Росії, ЄС та Україна відкладають тимчасове застосування ГВЗВТ (поглибленої та всеосяжної зони вільної торгівлі) до 1 січня 2019 року. Є помітні позитивні наслідки українського експорту до ЄС, обсяг якого зріс на 30 % у 2017 р. Структура експорту до ЄС змінилася на машини та обладнання, жири та олії рослинного чи тваринного походження, готові страви та продукти тваринного походження. Частка ЄС в українському експорті та імпорті також зросла через значне скорочення торгівлі з Росією. Застосування тарифних квот ЄС на сільськогосподарське виробництво зросло протягом 2014–2017 років, оскільки українські виробники поступово подолали проблеми з безпечністю харчових продуктів та слабким попитом на їхню продукцію. Європейський вибір є надзвичайно важливим фактором безперервної демократизації всіх цих трьох країн. Незважаючи на конкуренцію між європейською та євразійською ідентичностями, кожна з них вважає себе європейською країною. Вибір продовження шляху асоціації з Європою, зроблений цими країнами, незважаючи на очевидні політичні ризики (особливо серйозні для України), є найкращим свідченням їх реальної прихильності до європейського шляху розвитку.
Latkovskyi P. Problems and prospects of deepening EU-Ukrainian relations / P. Latkovskyi, A. Marushchak // Baltic journal of economic studies. - Vol. 5. - № 2. - Baltija Publishing, 2019. - Р. 96-103.
Keywords: European studies; Democracy Index; DCFTA; Ukrainian import; Ukrainian export; tariff quota; democratic choice; Європейські дослідження; індекс демократії; ПВЗВТ; український імпорт; український експорт; тарифна квота; демократичний вибір; Research Subject Categories::LAW/JURISPRUDENCE